(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses issues concerning the current state of activity and state policy in the economic development of service sector entities, analyzes the volume of the main indicators of business entities by economic sectors, the volume of services rendered by the main types of economic activity and regions.